Reakcija presadka proti gostitelju po transfuziji krvi in kako jo preprečimo - Barbarić Kovačić, Aleksandra (Zdravniški vestnik, 2021)
Transfusion associated graft versus host disease (TA-GvHD) is a rare but fatal complication of blood components transfusion therapy and has over 90% mortality rate. Transfused donor T lymphocytes react against the recipient's cellular and tissue antigens. Interaction triggers lymphocyte activation and, consequently, destruction of target cells in the recipient's tissues . The reason that immune cells of the recipient do not respond appropriately is an incompetent recipient's immune system and immunodeficiency of the host. Exceptionally, HLA compatibility between the donor and the recipient may cause the same reaction. Most effective way to prevent TA-GvHD is irradiation of the blood components with ionizing radiation. UVA psoralen based pathogen inactivation is an equally effective preventive measure of TA-GvHD, but it is applicable only to platelets. For this reason, it is important that physicians identify patients at risk of developing TA-GvHD and consequentially always prescribe irradiated blood units. Blood units that need to be irradiated are erythrocytes and granulocytes, with the mentioned exception of platelets. Fresh frozen plasma, cryoprecipitate, blood derived medicines, such as albumins, immunoglobulins, blood clotting factors, and erythrocytes after thawing are not irradiated. The recommended central field irradiation dose is 25-50 Gy.
Keywords: blood components; irradiation; krvni pripravki; obsevanje z ionizirajočimi žarki; TA-GvHD; transfuzija; zapleti